Recent pasture management determines biodiversity and productivity, and past management determines forage quality. Issue 3 (1st October 2016) - Yoshihara, Yu; Furusawa, Saya; Sato, Shusuke
ABSTRACT: Agro-ecosystem management focuses on developing grassland systems that meet sustainable productivity and biodiversity targets. Pasture management affects productivity and biodiversity, but the effects of previous management impacts are difficult to predict. Our objective was to identify the effects of key management factors and their timing on current biodiversity and productivity in public pastures in northeastern Japan. We surveyed pasture management histories (stocking rate, mowing frequency, fertilizer application and pasture renovation by plowing) from 1991 to 2010. We divided the data into periods and examined productivity, forage quality and biodiversity (plants and burrowing rodents). We included these parameters into generalized linear models, and found that recent fertilization level, mowing frequency and renovation were the most important factors affecting plant species diversity. In contrast, recent and past stocking rates were the dominant factors for productivity and forage quality, respectively. Thus, biodiversity and productivity were affected by different factors, suggesting that pasture management can balance the competing goals of biodiversity conservation and productivity improvement. From the effects of pasture management on biodiversity, forage productivity and quality, avoiding intensive pasture management is a practical application. In addition, a time lag effect of grazing pressure on forage quality should be considered during future pasture management.